2011
DOI: 10.1161/atvbaha.111.226167
|View full text |Cite
|
Sign up to set email alerts
|

Plaque Rupture and Thrombosis Are Reduced by Lowering Cholesterol Levels and Crystallization With Ezetimibe and Are Correlated With Fluorodeoxyglucose Positron Emission Tomography

Abstract: Lowering cholesterol levels with ezetimibe reduced plaque burden, crystallization, and inflammation, preventing plaque disruption and thrombosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 30 publications
4
27
0
Order By: Relevance
“…Hence, the current study provides the first such relationship between index inflammatory imaging and subsequent local plaque progression. Prior animal studies have shown that areas with high FDG uptake were associated with plaque thrombosis, 29,30 whereas human studies have shown that high aortic and carotid FDG uptake is related to subsequent risk of plaque rupture and clinical events. [31][32][33] However, in those studies, the relationship between location of inflammation and the location (or vessel bed) of the subsequent atherothrombotic event was not reported.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the current study provides the first such relationship between index inflammatory imaging and subsequent local plaque progression. Prior animal studies have shown that areas with high FDG uptake were associated with plaque thrombosis, 29,30 whereas human studies have shown that high aortic and carotid FDG uptake is related to subsequent risk of plaque rupture and clinical events. [31][32][33] However, in those studies, the relationship between location of inflammation and the location (or vessel bed) of the subsequent atherothrombotic event was not reported.…”
Section: Discussionmentioning
confidence: 99%
“…Local extracellular factors include a mild drop in local temperature, increased saturation of cholesterol, hydration of the cholesterol molecule and an alkaline milieu [ 20 ] . The formation of CCs is associated with an inflammatory response both locally and systemically [ 21- 22 ] . Crystals form early in the atherosclerotic process and activate the inflammasome NLRP3 leading to the secretion of IL-1β [ 22 ] .…”
Section: Pathogenesismentioning
confidence: 99%
“…Autopsy findings demonstrate that only patients who died of acute myocardial infarction had CCs perforating the intima while those who died of other causes and had significant arterial plaques did not have CCs perforating the intima [ 27 ] . In an atherosclerotic rabbit model, those with a greater plaque burden had more CCs, serum inflammation, macrophage infiltration and thrombosis [ 21 ] . Also, in the rabbit model, light and scanning electron microscopy demonstrated CCs in the inflamed fibrous cap and perforating the intima at the sites of plaque rupture [ 21, 28 ] .…”
Section: Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Cholesterol crystals are highly pathogenic as they can cause rupture of cell membranes 27 and of the intimal surface of the plaque at the tissue level. 28,29 Intracellular cholesterol crystals can promote NLRP3 inflammasome activation in macrophages. 30,31 Downstream, the NLRP3 complex activates caspase-1 that cleaves and releases active interleukin-1b, a major chemokine for leukocyte attraction.…”
Section: Unesterified Cholesterol and Crystal Formationmentioning
confidence: 99%